Analysis of Blood Flow and Urea Transport in Chitosan and Carbon Nanotube Dialyzer Membranes for Diabetic Haemodialysis - Md Nor Anuar Mohamad,; Halid, Mohammad Farhan; Mahbubi, Muharis; Taib, Ishkrizat; Yamamoto, Takahisa; Mazlan, Mohd Nizam; Martin, Awaludin (International Journal of Integrated Engineering, 2025)
Haemodialysis efficiency depends heavily on membrane characteristics, as material properties and thickness significantly influence blood flow behaviour and solute removal across the dialyzer. Despite advances in dialyzer design, there is limited comparative data on how membrane material and thickness affect blood flow dynamics and urea clearance, particularly under diabetic haemodialysis conditions. This gap hinders the selection of optimal membrane configurations for improved performance. This study investigates the performance of chitosan and carbon nanotube (CNT) dialyzer membranes through Computational Fluid Dynamics (CFD) simulations. A single-fibre dialyzer (SFD) model was developed using computational fluid dynamics (CFD) under transient, laminar, counter-current flow conditions. Three membrane thicknesses (0.15 mm, 0.18 mm, and 0.20 mm) were analysed for two materials: chitosan and CNT composites. The dialyzer geometry consisted of concentric cylindrical domains representing blood, membrane, and dialysate regions. Simulations showed that CNT membranes achieved higher maximum blood velocity (4.12 m/s) and wall shear stress (2.75 Pa) compared to chitosan membranes (3.91 m/s and 2.53 Pa, respectively) at 0.15 mm thickness. Pressure drops increased with membrane thickness for both materials, reaching up to 275 Pa at 0.20 mm. CNT membranes consistently outperformed chitosan in urea removal, reducing blood-side urea mass fraction from 0.02 to 0.00077 across all thicknesses, compared to a reduction to 0.00767 for chitosan at 0.20 mm. Overall, CNT membranes demonstrated superior flow uniformity and up to 96% urea clearance, maintaining efficiency even as thickness increased, while chitosan membranes showed decreased performance beyond 0.15 mm. These findings suggest that CNT membranes offer a more effective solution for haemodialysis, especially under diabetic flow conditions.